Some Thoughts on Literacy Issues in Indigenous Contexts - Nakata, Martin (The Australian Journal of Indigenous Education, 2003)
ABSTRACT This paper critically examines some elements of the nation’s policy on Indigenous education priorities (Department of Employment, Education and Training, 1989) and how they have framed our approaches to formal schooling issues over the past decade. I draw on some of the ‘cultural’ tensions in the policy position to illustrate the dilemma they produce at the level of practice. I then reflect on the implications of these tensions for literacy teaching as well as ways that they can be addressed. The conclusion brings these reflections back to a more theoretical level to consider how shifts at the level of theory might re-frame how we might best view the literacy issues and priorities in Indigenous contexts.